Гидродинамические характеристики стволов установок импульсного пожаротушения - Ivanitskiy, Александр (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
An overview of the problem of the use of extinguishing agent devices, and the results of the study the hydrodynamic characteristics of trunks of the fire extinguishing pulse installation are presented. Results of the study of fluid motion in the TFE–P trunk FPI–1 flow path and moving drops of spray jet in the air, derived from mathematical modeling and experimental study are discussed. A method for determining the hydrodynamic characteristics of liquid discharge from the trunks of fire extinguishing pulse installation, its software implementation, and experimental verification are also presented.